1989
DOI: 10.1002/1097-0142(19890815)64:4<842::aid-cncr2820640414>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis in estrogen receptor-positive human breast cancer takes place preferentially in estrogen receptor-negative cells

Abstract: The primary breast tumors of 27 patients were analyzed for the expression of estrogen receptors (ER) and DNA synthesis. Seventeen tumors were ER-positive, and the simultaneous expression of ER and DNA synthesis could be analyzed in 14 ER-positive tumors. DNA synthesis was measured through the thymidine labeling index (TLI). ER expression was detected by immunohistochemistry with monoclonal antibodies. In these tumors, 38.6% +/- 13.1% of the cells were ER-positive (average TLI = 0.60% +/- 0.70%), as opposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Mitotic frequency analyses (Aaltomaa et al, 1991a) and flow-cytometric analyses (Helin et al, 1989) have shown that the proliferation rate in steroid-receptor-negative tumours is about twice as high as in receptor-positive ones. Moreover, sophisticated analyses indicate that the synthesis of DNA takes preferentially place in steroid-receptor-negative cells in the otherwise receptorpositive tumours (Ballare et aL, 1989). The recent findings by Aaltomaa et al (1991b) showed that proliferation indices as well as classic prognostic factors have only limited predictive value in sex-steroid-receptor-negative tumours, findings which support the above data.…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic frequency analyses (Aaltomaa et al, 1991a) and flow-cytometric analyses (Helin et al, 1989) have shown that the proliferation rate in steroid-receptor-negative tumours is about twice as high as in receptor-positive ones. Moreover, sophisticated analyses indicate that the synthesis of DNA takes preferentially place in steroid-receptor-negative cells in the otherwise receptorpositive tumours (Ballare et aL, 1989). The recent findings by Aaltomaa et al (1991b) showed that proliferation indices as well as classic prognostic factors have only limited predictive value in sex-steroid-receptor-negative tumours, findings which support the above data.…”
Section: Discussionmentioning
confidence: 99%
“…computer-assisted microscopy) immunohistochemical methods (Cavaliere et al 1996;Charpin et al 1988a, b;Colley et al 1989;Lay®eld et al 1996) has allowed a better characterization of breast cancer heterogeneity in terms of ER + /ER ) and PgR + / PgR ) tumour cell distribution in a given breast cancer. This characterization of tumour heterogeneity can contribute signi®cant information to the determination of the absolute ER/PgR tumour content (Ballare et al 1989(Ballare et al , 1991Cavaliere et al 1996;Charpin et al 1988a, b;Colley et al 1989;Lay®eld et al 1996;Seymour et al 1990). This means that it is now possible to distinguish between a tumour with a large number of ER + cells but with a small quantity of ER per cell and a tumour containing few ER + cells but with a large amount of ER per cell; both are able to produce the same absolute ER value in a biochemical assay.…”
Section: Discussionmentioning
confidence: 99%